The outweigh of toxicity versus risk of recurrence for adjuvant interferon therapy: a survey in German melanoma patients and their treating physicians - Kähler, Katharina C.; Blome, Christine; Forschner, Andrea; Gutzmer, Ralf; Hauschild, Axel; Heinzerling, Lucie; Livingstone, Elisabeth; Loquai, Carmen; Müller-Brenne, Tina; Schadendorf, Dirk; Utikal, Jochen; Wagner, Tobias; et al. (Oncotarget, 2018)
After more than two decades with interferon alfa-2a and 2b (IFN) as the only approved drugs in the adjuvant setting for melanoma, new treatment approaches like immune checkpoint inhibitors and BRAF-MEK inhibitors improve the progression free survival (PFS) and also the overall survival (OS). We compared physicians' preferences ("utilities") for health states associated with IFN therapy to their patients' preferences. Utilities describe a preference for a specific health state on a scale of 0 (as bad as death) to 1.0 (perfect health). Setting: We assessed utilities for health states associated with adjuvant IFN using the standard gamble technique in 108 physicians and 130 melanoma patients. Four IFN toxicity scenarios and three outcome scenarios were given to the participants. Both groups were asked for the 5-year disease free survival (DFS) they would need to accept the described IFN-related side effects. Results: In both groups, utilities for melanoma relapse were significantly lower than for IFN side effects, showing that toxicity was more acceptable than relapse. Physicians indicated higher utilities for each scenario and needed lower 5-year DFS both in case of mild-to-moderate and severe side effects. Patients were willing to tolerate mild-to-moderate and severe toxicity for a 50% and 75% chance of 5-year DFS, while physicians only required a chance of 40% and 50%, respectively. Conclusion: Both physicians and patients rated melanoma recurrence much lower than even severe IFN side effects. In direct comparison, physicians rated cancer-related scenarios more positively and accepted IFN toxicity for an even lower treatment benefit.
EVALuna2:34416